Evidence for an unorthodox firing sequence employed by the Berlin Painter: deciphering ancient ceramic firing conditions through high-resolution material characterization and replication. Issue 3 (22nd December 2014) - Cianchetta, I.; Trentelman, K.; Maish, J.; Saunders, D.; Foran, B.; Walton, M.; Sciau, Ph.; Wang, T.; Pouyet, E.; Cotte, M.; Meirer, F.; Liu, Y.; et al.
Abstract : The firing conditions used to produce an Athenian vessel in the 5th century B.C. were determined by XANES spectroscopy. Abstract : XANES spectroscopy was used to complement the results previously obtained with Raman spectroscopy by the same group to determine the firing conditions used in the production of a single vessel painted by the Berlin Painter in the 5th century B.C. The vessel, part of the collection of the J. Paul Getty Museum, presents a complicated layered architecture of black and red gloss, with different stratigraphies present on the interior and exterior surfaces. The study of two samples, one each from the interior and exterior surface of the vessel, was performed with the complementary analytical techniques of X-ray nano- and micro-spectroscopy (X-ray fluorescence spectroscopy (XRF) and full-field transmission X-ray micro-spectroscopy (FF-XANES) across the Fe K edge), and supported by a replication study. The replicates, made in a laboratory furnace providing complete control over the firing temperature and oxygen partial pressure, provided a paradigm for the comparison of the mineralogical phases observed in the ancient samples, which led to a deeper understanding of the firing conditions necessary for the production of the Berlin Painter's vessel. Our results confirm the necessity of multiple firings and painting applications to obtain the Berlin Painter's architecture and provide a further example of the multiplicity of techniques and practices employed by the potters of the Kerameikos in ancient Athens.